How to use finite differences to determine an equation?

  X | Y

-3  | 0

-2  | 15

-1  | 16

0   | 9

1   | 0

2   | -5

3   | 0

Expert Answers

An illustration of the letter 'A' in a speech bubbles

If the data given is generated by a polynomial, then we can use the method of finite differences to find the degree of the polynomial. Since the x values all differ by one, consider the y-values:

0      15      16      9      0      -5      0    Now take the difference
   \  /     \  /     \  /    \  /    \  /    \  /
    15       1       -7     -9     -5      5
        \  /     \  /     \  /    \  /    \  /
        -14     -8      -2      4      10
              \ /      \/      \/      \/
               6       6       6       6

Since the third order differences are the same, the generating polynomial is a cubic.

The general cubic is `y=ax^3+bx^2+cx+d` Substituting known x,y pairs we create a system of linear equations; here use (0,9),(1,0),(2,-5) and (3,0):

0a+0b+0c+d=9 ==> d=9

 a+ b+ c+ 9=0  Using x=1,y=0 and d=9
8a+4b+2c+9=-5 Using x=2,y=-5 and d=9
27a+9b+3c+9=0 Using x=3,y=0,d=9

We have three equations and three unknowns. Solve the system (there are a number of methods: inverse matrices, Cramer's rule, Gaussian elimination, Gauss-Jordan row reduction, linear combinations, substitution, or technology come to mind.) Or you could see that you have three zeros so the function factors as

`y=(x+3)(x-3)(x-1)`  ** if -3 is a zero, x+3 is a factor.

------------------------------------------------------------------

The function we seek is `y=x^3-x^2-9x+9` or `y=(x-3)(x+3)(x-1)`

------------------------------------------------------------------

A formula that you will not have learned in class. Start at x=0. The y-value is 9. Now go along the diagonal of the finite differences from 9 -- you get 9,-9,4,6. According to a formula from Newton, the formula for the nth number of the sequence we are studying is given by:

`a+bn+(cn(n-1))/2+(dn(n-1)(n-2))/(2*3)+...` where a is the y-value for x=0, and b,c,d,... are the numbers along that diagonal.

Substituting a=9,b=-9,c=4 and d=6 (going further the finite differences are zero and thus do not contribute anything) we get:

`9-9n+(4n(n-1))/2+(6n(n-1)(n-2))/6`

`=9-9n+2n^2-2n+n^3-3n^2+2n`

`=n^3-n^2-9n+9` as we got above.

``

``

``

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial